ANALISIS PEMANFAATAN PLATFORM MERDEKA MENGAJAR UNTUK PENINGKATAN KOMPETENSI GURU DI SEKOLAH MENENGAH ATAS AL MUHAMMAD CEPU - Puspita Sari, Kharisma; Sariman, Sariman; Mujahidin, Moh (https://www.ejournal.smaamc.sch.id/index.php/belajar, 2023)
This research aims to analyze the use of the Merdeka teaching platform to improve the competency of teachers at Al Muhamamd Cepu High School. This type of research is a descriptive qualitative approach, with data sources from school principals, teachers and other documents. The results of this research are that most of the Al Muhamamd Cepu High School teachers have worked on the topics in the PMM application, and a small number have taken real action and received certificates. This requires special motivation and attention from both leaders and teachers to complete the PMM so that it can be achieved. increase understanding and produce work on the implementation of the Merdeka curriculum so that teacher competence can continue to be honed and improved